PLANTS VISITED BY Apis mellifera L. (HYMENOPTERA: APIDAE) IN RECÃ”NCAVO BAIANO, STATE OF BAHIA, BRAZIL - Santos do Nascimento, Andreia; Lopes de Carvalho, Carlos Alfredo; Lacerda Lopes Martins, MÃ¡rcio (REVISTA DE AGRICULTURA, 2014)
The objective of this study was to identify the plants visited by Apis mellifera L. (Hymenoptera: Apidae) in the region of RecÃ´ncavo Baiano, State of Bahia, Brazil. Flowering plants were assessed in a radius of 1.500 m around the apiaries visited. A total of 240 species belonging to 171 genera and 50 families were recorded. The family Leguminosae had the highest species richness (22%), followed by Asteraceae (14%) and Malvaceae (7%) of all plant species visited by Apis mellifera. The highest percentage of plants collected had herbaceous growth habit (44%), followed by woody plants (26%) and shrubs (18%). Lianas, vines and palm trees were significantly less represented. It was found that 65% of species hadÂ Â actinomorphic flowers and 33% had zygomorphic flowers. The genera that showed higher diversity were Sida with nine species, Croton with six species, Senna with five species, while Chamaecrista, Eucalyptus, Eupatorium, Ocimum, Passiflora and Vernonia were represented by four species each. The flora of apicultural interest in the region of RecÃ´ncavo Baiano has a wide range of species with varying growth habits.